Dense Plasma focus experimentation in the “COVID-19” environment - Arwinder, Singh; Teh, Thiam Oun; Saw, Sor Heoh; Lee, Sing (INTI International University, 2021)
In today’s world of the “COVID-19 endemic”, movement control order has been enforced in a majority of countries all over the world. This severely restricts access to universities and research facilities. In this paper, Lee’s model code which was developed by one of the coauthors, is shown to simulate Tsinghua University Plasma Focus machine of Beijing China. Such numerical experiments are a good stop-gap measure until we can access our laboratories again. Our code requires only a measured current waveform from the actual machine. The computed current waveform is fitted to the measured current waveform by fine-tuning the model parameters. Once fitted, realistic dynamics is generated giving a good understanding to the plasma conditions in the machine. Importantly, we demonstrate that the neutron yield computed from this code agrees reasonably well with the published measurements.